2014
DOI: 10.1037/a0035929
|View full text |Cite
|
Sign up to set email alerts
|

Chinese American parents’ acculturation and enculturation, bicultural management difficulty, depressive symptoms, and parenting.

Abstract: This study examined whether Chinese American parents’ acculturation and enculturation were related to parenting practices (punitive parenting, democratic child participation, and inductive reasoning) indirectly through the mediation of parents’ bicultural management difficulty and parental depressed mood. Data came from a two-wave study of Chinese American families in Northern California. Mothers and fathers were assessed when their children were in early adolescence and then again in middle adolescence (407 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(58 citation statements)
references
References 42 publications
6
52
0
Order By: Relevance
“…Results demonstrate that having a father with a Chinese profile had a negative effect on adolescents’ GPA trajectories. This is consistent with prior work on acculturation and parenting, which indicates that a lack of involvement with the mainstream American culture may make it difficult for parents to be involved in the educational system (Jeonga & Acock, 2014; Turney & Kao, 2009); acculturation difficulties may also engender stress, hindering parents’ ability to support their children’s school work (Costigan & Koryzma, 2011; Kim, Shen, Huang, Wang, & Orozco-Lapray, in press). Interestingly, parental Chinese-oriented acculturation profiles had a negative impact on adolescents’ GPA trajectories only in the case of fathers.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Results demonstrate that having a father with a Chinese profile had a negative effect on adolescents’ GPA trajectories. This is consistent with prior work on acculturation and parenting, which indicates that a lack of involvement with the mainstream American culture may make it difficult for parents to be involved in the educational system (Jeonga & Acock, 2014; Turney & Kao, 2009); acculturation difficulties may also engender stress, hindering parents’ ability to support their children’s school work (Costigan & Koryzma, 2011; Kim, Shen, Huang, Wang, & Orozco-Lapray, in press). Interestingly, parental Chinese-oriented acculturation profiles had a negative impact on adolescents’ GPA trajectories only in the case of fathers.…”
Section: Discussionsupporting
confidence: 86%
“…Given their traditional role as the breadwinner and head of the family (Roer-Strier, Strier, Este, Shimoni, & Clark, 2005), fathers with a Chinese profile may experience more adaptation stress compared to those with an American or Bicultural profile. This stress may compromise fathers’ ability to fulfill their parenting roles (Kim et al, in press), which may explain the faster decrease in GPAs observed among adolescents with Chinese-profile fathers.…”
Section: Discussionmentioning
confidence: 99%
“…S. Kang et al, 2014), cultural orientations (e.g., S. H. Chen, M. Hua, et al, 2014; S. Y. Kim, Shen, Huang, Wang, & Orozco-Lapray, 2014), and acculturation profiles (e.g., S.…”
Section: Resultsmentioning
confidence: 99%
“…Empirical findings on the relations between cultural orientations and family processes have largely focused on the parent-child acculturation gap (but not cultural orientations per se) and its impact on relationships, typically parent-child conflict (e.g., Choi et al, 2008; Dinh & Nguyen, 2006; Farver, Narang, & Bhada, 2002; Lau et al, 2005; Ying & Han, 2007) or parenting practices (e.g., S. Y. Kim, Shen, Huang, Wang, & Orozco-Lapray, 2014).…”
Section: Cultural Orientation and Youth Perception Of Family Processesmentioning
confidence: 99%